2013
DOI: 10.1111/resp.12150
|View full text |Cite
|
Sign up to set email alerts
|

Variability and consistency in lung inflammatory responses to particles with a geogenic origin

Abstract: The unique physicochemical characteristics of geogenic particles induced a proinflammatory response in the lung. These data suggest that particle composition should be considered when setting community standards for PM exposure, particularly in areas exposed to high geogenic particulate loads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 35 publications
4
39
1
Order By: Relevance
“…Filters were then dried overnight leaving the b10 μm fraction for our in vivo experiments. We have previously shown that the physico-chemical attributes of this extracted PM 10 closely matches that of the airborne PM 10 from the same sites (Zosky et al, 2014a).…”
Section: Sample Collectionmentioning
confidence: 59%
See 4 more Smart Citations
“…Filters were then dried overnight leaving the b10 μm fraction for our in vivo experiments. We have previously shown that the physico-chemical attributes of this extracted PM 10 closely matches that of the airborne PM 10 from the same sites (Zosky et al, 2014a).…”
Section: Sample Collectionmentioning
confidence: 59%
“…The 100 μg dose was chosen based on our previous dose-response data (Zosky et al, 2014a) and prior work on diesel particles (Boylen et al, 2011;Larcombe et al, 2013) showing that particle loads in macrophages are equivalent to those observed in human macrophages (Kulkarni et al, 2006). Control mice received 50 μL of saline alone.…”
Section: In Vivo Exposure Modelmentioning
confidence: 99%
See 3 more Smart Citations